Fa’atsiru Faqlidu Rokat Tase ‘ala ‘aqidatu as-shiyadin - Farhah Farhah; Nada Haninah Saifurrahman* (Journal of Comparative Study of Religions, 2021)
Rokat Tase’ is a tradition or ancestral heritage that is still preserved by coastalcommunities, especially fishermen. In its implementation, several rituals havebecome their beliefs which have a major influence on the faith of the local community.One of the rituals in this tradition is Larung Sesaji. This ritual is also one of the relicsof the teachings of Hinduism, which is still preserved by the ancestors to date,leaving an impact on the fishermen. This article will discuss the implementation ofRokat Tase ‘in Pakandangan Barat village, Sumenep Madura and its influence onfishermen. Rituals in Rokat Tase’ begin with khatam al-Quran and continue withistighasah, tahlilan, Larung Sesaji that are paraded to the sea in a boat. The a Sesajenwere dissolved in the form of food and goods placed in a small boat called Bithek.This ritual is not following the teachings of Islam. Besides that, there is also an artperformance and ends with tabligh akbar. Rokat Tase’s implementation affects thefaith of the fishermen in Pakandangan Barat village, Sumenep, Madura.